Lesotho Digital Economy Diagnostic - World Bank (World Bank, Washington, DC, 2020)
Lesotho is a landlocked country with a population of about 2.0 million people. Lesotho’s private sector makes limited use of digital technologies. In the private sector, digital technology can change the way economies of scale are achieved, particularly through e-commerce and digital payments. The digital economy may provide the better matching of buyers and sellers in a competitive marketplace. The digital economy offers potential for enhanced service delivery in the public sector, but the Lesotho government’s efforts in this field appear fragmented and slow moving. Improved digital infrastructure can only achieve the desired transformational impact if combined with a capable public sector, investments in digital skills and literacy, increased access to digital financial services, and ramped up support for digital start-ups and existing businesses. A holistic view to developing the digital economy is required. This report will provide a diagnostic and offer recommendations on the five foundations of the digital economy in Lesotho. The report will examine, in turn, challenges concerning the policy and legal environment, digital infrastructure, public digital platforms, private digital platforms, digital financial services, digital entrepreneurship, and digital skills. This report reviews how the digital divide affects the foundations of the digital economy and provides policy options for bridging the digital divide.